2004
DOI: 10.1002/eji.200425050
|View full text |Cite
|
Sign up to set email alerts
|

Frontline: Epitope recognition on the myelin/oligodendrocyte glycoprotein differentially influences disease phenotype and antibody effector functions in autoimmune demyelination

Abstract: Preliminary observations of humoral immunity against the myelin oligodendrocyte glycoprotein (MOG) in experimental allergic encephalomyelitis (EAE) and human multiple sclerosis (MS) suggest that a subset of anti-MOG autoantibodies directed against conformational epitopes is of pathogenic predominance. Here, we provide proof that in marmoset EAE, autoantibodies reactive against conformational epitopes of MOG are not only responsible for aggravating demyelination, but also an essential factor for disease dissemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
95
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 41 publications
5
95
1
1
Order By: Relevance
“…However, it is possible that the epitopes recognized by MS-mAb may depend on their intact conformation and/or posttranslational modifications. In the case of anti-MOG antibodies, for example, it has been shown that demyelinating anti-MOG antibodies recognize conformational epitopes [7] or glycosylated MOG [28]. Furthermore, epitopes of lipids, which have also been described to be target antigens of humoral immune responses in MS [39,40], would not be appropriately represented by Western blotting or phage display techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible that the epitopes recognized by MS-mAb may depend on their intact conformation and/or posttranslational modifications. In the case of anti-MOG antibodies, for example, it has been shown that demyelinating anti-MOG antibodies recognize conformational epitopes [7] or glycosylated MOG [28]. Furthermore, epitopes of lipids, which have also been described to be target antigens of humoral immune responses in MS [39,40], would not be appropriately represented by Western blotting or phage display techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, clonally restricted Ig genes suggesting the presence of an antigendriven immune response have been found in MS lesion tissue [4]. In animal models of MS, namely experimental autoimmune encephalomyelitis in rodents and primates, CNS myelin-specific autoantibodies against myelin oligodendrocyte glycoprotein (MOG) have been demonstrated to possess myelin-destructive potential [5][6][7]. Antibody responses against MOG and other myelin proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that this lack of concordance between different studies is due to the inability of most assay methods to differentiate between pathogenic (demyelinating) and nonpathogenic MOG-specific Abs. Experimental animals mount a complex Ab response to the extracellular domain of MOG (MOG ex ) that targets both linear as well as discontinuous, conformational epitopes (22)(23)(24). Crucially, only conformation-dependent MOG-specific Abs are able to initiate demyelination in EAE (22)(23)(24).…”
mentioning
confidence: 99%
“…Experimental animals mount a complex Ab response to the extracellular domain of MOG (MOG ex ) that targets both linear as well as discontinuous, conformational epitopes (22)(23)(24). Crucially, only conformation-dependent MOG-specific Abs are able to initiate demyelination in EAE (22)(23)(24). In contrast, Abs directed against linear MOG ex -peptide epitopes are unable to bind to the native protein at the membrane surface and fail to induce any significant pathology in vivo.…”
mentioning
confidence: 99%
“…The sample size is too small to make any definitive conclusions but this observation does raise the possibility that antibodies bind to MOG epitopes that are generated during the MBP-induced inflammatory response. If this is the case, this antibody response (together with antibodies recognizing other exposed determinants) may influence lesional pathology by accelerating the clearance of myelin debris from the lesions by activated macrophages.However, the MOG-specific antibody response in patients with MS recognizes a far more complex repertoire of linear epitopes [33,47] than marmosets [36] or rodents [26-28, 46, 48] do. This peptide-specific response in man does not recognize the native protein [33] and is therefore unlikely to mediate demyelination in vivo, but further studies are required to determine whether or not these responses have any other pathological significance.…”
mentioning
confidence: 99%